2014
DOI: 10.1038/nm.3626
|View full text |Cite
|
Sign up to set email alerts
|

The ribonuclease activity of SAMHD1 is required for HIV-1 restriction

Abstract: The HIV-1 restriction factor SAMHD11,2 is proposed to inhibit HIV-1 replication by depleting the intracellular dNTP pool3-5. However, the phosphorylation of SAMHD1 regulates its ability to restrict HIV-1 without decreasing cellular dNTP levels6-8, which is not consistent with a role for SAMHD1 dNTPase activity in HIV-1 restriction. Here, we show that SAMHD1 possesses RNase activity and that the RNase but not the dNTPase function is essential for HIV-1 restriction. By enzymatically characterizing Aicardi-Goutiè… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
296
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(319 citation statements)
references
References 29 publications
17
296
6
Order By: Relevance
“…The majority of the mutations were predicted to be deleterious by using in silico analysis: 87% were predicted to be damaging by at least one of four computational tools (Grantham, SIFT, PolyPhen2, and CADD), 72% by two or more tools, and 50% by three tools (Table S1) (37)(38)(39)(40). Four of the mutations (R145, D207, R366, and R451) are located at amino acid residues that have been reported to have functional significance in in vitro studies (27,41,42).…”
Section: Samhd1mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the mutations were predicted to be deleterious by using in silico analysis: 87% were predicted to be damaging by at least one of four computational tools (Grantham, SIFT, PolyPhen2, and CADD), 72% by two or more tools, and 50% by three tools (Table S1) (37)(38)(39)(40). Four of the mutations (R145, D207, R366, and R451) are located at amino acid residues that have been reported to have functional significance in in vitro studies (27,41,42).…”
Section: Samhd1mentioning
confidence: 99%
“…Initially, the restriction function of SAMHD1 was attributed to its dNTPase activity, which was presumed to decrease the intracellular dNTP concentrations to levels incompatible with viral replication (26). Later, it was suggested that restriction of HIV-1 was primarily caused by the nuclease activity of SAMHD1 degrading viral RNA (27). However, more recently it was proposed that SAMHD1 lacks nuclease activity altogether and that the restriction of HIV-1 is caused by alternating ssRNA-binding and dNTPase activities (28).…”
mentioning
confidence: 99%
“…The catalytic activity is regulated by nucleoside triphosphate binding at two allosteric sites, which induces the formation of a stable tetramer [1]. In addition to the well-established dNTPase activity, single stranded nucleic acid binding [2] and in vitro nuclease activity were reported [3,4]. However, later data attributed the nuclease activity to contaminants co-purifying with SAMHD1 and the question of SAMHD1 harboring multiple functions is still debated [5].…”
Section: Introductionmentioning
confidence: 99%
“…SAMHD1 is highly expressed in myeloid cell types like DCs and macrophages (30). SAMHD1 contains a dNTPase and an RNase domain and limits synthesis of HIV-1 cDNA in these cell types by depletion of the intracellular dNTP pool or its RNase activity (31)(32)(33)(34)(35). It was previously shown that degrading SAMHD1 by treating DCs with SIV-Vpx leads to infection of DCs and subsequent DC maturation (29).…”
mentioning
confidence: 99%